Night of soldiers and spies - Messner, Kate; McMorris, Kelley (New York, NY : Scholastic Inc., 2019)
Ranger the time-travelling Golden retriever and young Isaac Pope come together in 1776 during Washington's retreat after the Battle of Long Island, and Ranger stays with Isaac while he slowly recovers from Smallpox--but Ranger's real mission comes later when Isaac is sent to spy out the Hessian troops' intentions before the Battle of Trenton.
Keywords: Golden retriever -- Juvenile fiction; Time travel -- Juvenile fiction; Soldiers -- Juvenile fiction; Smallpox -- Juvenile fiction; Espionage, American -- Juvenile literature; Long Island, Battle of, New York, N.Y., 1776 -- Juvenile fiction; Trenton, Battle of, Trenton, N.J., 1776 -- Juvenile fiction; Adventure stories; Golden retriever -- Fiction; Dogs -- Fiction; Time travel -- Fiction; Smallpox -- Fiction; Spies -- Fiction; Adventure and adventurers -- Fiction; Long Island, Battle of, New York, N.Y., 1776 -- Fiction; Trenton, Battle of, Trenton, N.J., 1776 -- Fiction; United States -- History -- Revolution, 1775-1783 -- Fiction; United States -- History -- Revolution, 1775-1783 -- Juvenile fiction; Adventure fiction; Historical fiction; Action and adventure fiction